An example for Mobile Internet applications in agriculture - Szilágyi, Róbert; Lengyel, Attila (Acta Agraria Kaposváriensis, 2006)
There are already several applications on mobile devices that can be useful in agriculture. For example GPS-enabled map software and even other, more complex agricultural systems. These are just beginning to spread in the Hungarian agrifood sector. The possibility of using mobile Internet and mobile tools for agribusiness is increasing. Mobile tools are really suitable for tasks like inspecting the evolution of prices of agricultural products. An application developed by us is a mobile extension to access the Market Price Information System run by the Hungarian Agricultural Economics Research Institute. The accessibility of information demanded by market actors can be ensured effectively by using mobile tools. The biggest limitation for mobile devices is screen size.
Keywords: mobile Internet; mobile application; WAP